ASSESSMENT OF THE ROLE OF INSTITUTIONAL PARTICIPANTS IN THE PROCESS OF POST-SPORTS ADAPTATION - Ryskin, Petr; Fagina, Stanislav; Shuraleva, Natalia (Revista Inclusiones, 2020)
The subject of the study is the assessment by professional athletes of the participation of institutions in the processes of post-sports adaptation, including government bodies, sports federations and professional teams. As research methods, we used a survey of athletes at the stage of completing a sports career and the results of an analysis of the data obtained during group discussions on the theme “Character, features and difficulties of post-sports adaptation of professional athletes in modern Russia”. 4 discussions were held, 2 in 2016, 2 in 2019, they were attended by International Masters of Sports, as well as Honored Masters of Sports, includingseveral participants of the Olympic Games (sports -boxing, athletics, rock climbing; sea all-around, swimming, judo, sambo, classic wrestling, football, weightlifting). The study revealed that the Sports Federation, State authorities and local governments, sports organizations, teams and other “institutions” provide assistance in the processes of post-sports adaptation in less than 7% of cases.